Komposisi Kimia dan Beberapa Sifat Fungsional Protein Paru Sapi yang Diekstraksi Dengan Metode Alkali (Jurnal Ilmu dan Teknologi Hasil Ternak, 2015)
This research was carried out to examine the functional properties of beef lung protein concentrates. The extraction was performed as a function of pH and time. The pI method was applied in the precipitation of proteins from beef lung. Beef lung protein concentrates contained 85.13% protein. The functional properties of the protein concentrates were compared to those of some commercial ingredients as whey protein concentrates, and casein. Protein from beef lung exhibited better foaming property than casein and better emulsifying property than whey protein. The use of beef lung proteins appears to be an interesting opportunity to obtain added value slaughterhouse by-products.